PENGARUH ARUS KAS BEBAS, HUTANG DAN LABA TERHADAP DIVIDEN PADA PERUSAHAAN MANUFAKTUR YANG TERCATAT DI BURSA EFEK INDONESIA TAHUN 2012-2014 - Lidya Ayu Purnamasari (Manajemen Bisnis, 2016)
The purpose of this research is to know and analyze the effect of variable free cash flow (FCF), debt (DAR) and earnings (EPS) of dividends (DPR), and determine which variables are most effect on the dividend. This type of research is explanatory research with quantitative approach and using multiple regression analysis with a sample of manufacturing companies listed in Indonesia Stock Exchange that cash dividends for three years, have complete data, and does not have a negative net income during the years 2012-2014. Based on the results of the research indicated that the variable free cash flow (FCF), debt (DAR) and earnings (EPS) significantly affects the dividend (DPR), which is reinforced by F test and t test. The results of the f test (simultaneous) indicate that third variable indepen (free cash flow, debt and profit) together affect dividends significantly. The results of the t test (partial) indicates that the variable free cash flow positive effect is not significantly to dividends. Variable debt negative effect is not significanly to dividend and variable profit significant positive effect on the dividend. The variables that most influence on dividends are variable profit.